Is Surgical Removal of Asymptomatic Third Molars in the Horizontal III-C Position Advisable? A Pilot Study of Tomographic Evaluation - João Paulo da Silva Guilherme; Marcelo Santos Bahia; Yuri de Lima Medeiros; Marcella Yumi Kadooka; Marcelo Tarcísio Martins; Isabel Cristina Gonçalves Leite; Marcos Vinicius Queiroz de Paula (eJournal of Oral Maxillofacial Research)
Objectives: This cross-sectional study aimed to measure the distance between the buccal and lingual cortical bones and its relation with the mandibular canal roof of third molars classified as III-C position according to Winter, Pell and Gregory classifications in cone-beam computed tomography.